Testimonials, endorsements and celebrities in advertising. An empirical study of advertising strategies at the Cannes Lions International Festival of Creativity, 2010-2020 - Fernández Gómez, Jorge David (2022)
This work addresses the concepts of testimonials, endorsement and celebrities from an advertising strategy and brand management perspective. Our goal is to study the way in which advertisers and advertising companies have used testimonials and the image of celebrities with commercial or corporate purposes in the context of advertisements included in the Cannes Film Festival from 2010 to 2020, within the Iberoamerican sphere. In order to do this, a content analysis was carried out of 280 pieces. In addition to quantifying the presence and strategic implications of the use of celebrities, it also provided data and conclusions concerning the endorsement technique and the use of advertising testimonials in general. Strategic positioning, types of objective, way of endorsement and celebrities characteristics have been analyzed. Results indicate that testimonials have been used in 41,1% of the commercials, highlighting the common person (62,1%), followed by the celebrity (25,0%). Strategically, hybrid purposes are important (48,3%), user positioning (55,17%) and attributes (42,2%). And the co present mode as the principal way of endorsement (89,3%). According to celebrities characteristics, it can underline familiarity (76,9%), the unique character (51,9%), generation of interest (42,3%) and fame (34,6%). This research concludes the relevance of testimonials in Iberoamerican advertising, in the way that types of endorsement and use of testimonials have strategic implications for branding.